What the Pollution Havens Debate Overlooks - Jennifer Clapp (Global Environmental Politics, 2002)
Whether or not pollution havens exist in poor countries has been the subject of a great deal of debate in recent decades. This concern is warranted, as the intensity of dirty industry is rising in the developing world just as it is falling in the industrialized world. But identifying pollution havens is extremely difficult in practice. Part of the reason for this is that there are important flaws with the methods and measures used in the pollution havens literature which results in an overly narrow debate. It may be time to abandon the narrowly constructed pollution havens debate in favor of a more open-ended analysis of the linkages between global trade and investment and environmental regulation.